Revisiting multipoint relay selection in the optimized link state routing protocol. (1st December 2008) - Gantsou, Dhavy; Sondi, Patrick; Hanafi, Sa?d
The objective of the multipoint relay (MPR) technique is to reduce the number of redundant retransmissions, while ensuring reliable delivery of broadcast messages in wireless networks. To do this, it is necessary to select a small set of re-transmitter nodes, called multipoint relays. Selecting multipoint relays is a fundamental operation in the optimized link-state routing (OLSR) protocol. Research on MPR selection commonly focuses on heuristics. We propose to model MPR selection as a mixed-integer program. Solving this model optimally provides the means to accurately analyse and compare MPR selection heuristics. We also propose a new method for exploring the graph model of the network in order to satisfy the required constraints optimally. We call this exploration method reversible marking. We then combine this reversible marking mechanism with the simple greedy heuristic to create a new OLSR-compliant MPR selection heuristic. Testing has shown that our heuristic offers a good compromise between the need to minimise the number of MPR and the need to insure good coverage.